The common sense guide to improving palliative care - Lynn, Joanne, 1951- (Oxford University Press, 2007)
Improving care for patients in the last phase of their life has been a field that most health care providers have struggled with during last few years. Having worked with hundreds of providers throughout the country, these experienced authors know what providers need when it comes to implementing a quality improvement project. The guide provides user-friendly, step-by-step instructions on how to implement a quality improvement project in a broad variety of settings. Instructions are brought to life with specific examples from actual successful projects and and based on best practices in the in.